Preliminary Evidence of Orthostatic Intolerance and Altered Cerebral Vascular Control Following Sport-Related Concussion - Worley, Morgan L.; O'Leary, Morgan C.; Sackett, James R.; Schlader, Zachary J.; Willer, Barry; Leddy, John J.; Johnson, Blair D. (Frontiers in Neurology, 2021)
Concussions have been shown to result in autonomic dysfunction and altered cerebral vascular 23 function. We tested the hypothesis that concussed athletes (CA) would have altered cerebral 24 vascular function during acute decreases and increases in blood pressure compared to healthy 25 controls (HC). Ten CA (age: 20±2 y, 7 females) and ten HC (age: 21±2 y, 6 females) completed 26 5 min of lower body negative pressure (LBNP; -40 mmHg) and 5 min of lower body positive 27 pressure (LBPP; 20 mmHg). Protocols were randomized and separated by 10 min. Mean arterial 28 pressure (MAP) and middle cerebral artery blood velocity (MCAv) were continuously recorded. 29 Cerebral vascular resistance (CVR) was calculated as MAP/MCAv. Values are reported as 30 change from baseline to the last minute achieved (LBNP) or minute 5 (LBPP). There were no 31 differences in baseline values between groups. During LBNP, there were no differences in the 32 change for MAP (CA: -23±18 vs. HC: -21±17 cm/s; P=0.80) or MCAv (CA: -13±8 vs. HC: -33 18±9 cm/s; P=0.19). The change in CVR was different between groups (CA: -0.08±0.26 vs. HC: 34 0.18±0.24 mmHg/cm/s; P=0.04). Total LBNP time was lower for CA (204±92 s) vs. HC 35 (297±64 s; P=0.04). During LBPP, the change in MAP was not different between groups (CA: 36 13±6 vs. HC: 10±7 mmHg; P=0.32). The change in MCAv (CA: 7±6 vs. HC: -4±13 cm/s; 37 P=0.04) and CVR (CA: -0.06±0.27 vs. HC: 0.38±0.41 mmHg/cm/s; P=0.03) were different 38 between groups. CA exhibited impaired tolerance to LBNP and had a different cerebral vascular 39 response to LBPP compared to HC.